Open access and open data on natural disasters. (March 2017) - De Giusti, Marisa R.; Villarreal, Gonzalo L.; Nusch, Carlos J.; Pinto, Analía V.; Lira, Ariel J.
After a flood which devastated the city of La Plata (Argentina) in April 2013, a survey of the water situation in the region revealed that relevant studies and projects related with this area were scattered and lacked visibility. This prompted academic, scientific, technologic, and governmental institutions to take action and work together to compile, organize, and disseminate available data in an unprecedented response to an environmental disaster in the region. For this purpose, a dedicated collection was created in the SEDICI, the institutional repository for the Universidad Nacional de La Plata, and subsequently, the Observatorio Medioambiental La Plata (OMLP), a repository for data on environmental research, was launched. This document describes these collaboration initiatives which aim to anticipate and reduce the impact of natural disasters, their main characteristics, their resources, and their current progress. Projects driven by the OMLP are also described, along with a description of their technical and infrastructure deployment as per the open access policies.